Smart Technologies: Unique Opportunities Or The Global Challenges Of Transhumanism - Vorontsova, Yulia; Arakelyan, Artur; Baranov, Vladimir (Տիգրան Մեծ)
The article is devoted to issues related to the creation and use of innovative breakthrough technologies. At the present stage of transhumanistic concept implementation, it is necessary to consider its reflection in various fields of scientific knowledge. This concept has been recently arousing genuine interest both in its direction and in its contradictions. Today, there is a discussion around this, which allows us to evaluate all the “pros” and “cons” of a transhumanistic idea implementation, which requires improving the physical condition of a person by using the most advanced technologies, among which an important place is taken by biotechnologies, artificial intelligence and other Smart technologies. Their use generates contextual social, economic, and political problems. Therefore, the authors propose an interdisciplinary approach to assess various types of transhumanism challenges, taking into account the use of their unique capabilities while minimizing the risks associated with this. This aspect is proposed to be considered using the mechanism that forms the risk expanse and tools for working with it.
Keywords: Digital economy